The Effect of English Songs on Fifth Grade Students’ Motivation in Vocabulary Mastery at MI MA’ARIF SURENGEDE KERTEK - Muhammad Arvan Ibrahim; Arif Widyantoro (Metaphor, 2025)
Vocabulary mastery plays a vital role in supporting students' language skills, especially in English learning at the elementary school level. However, many students still struggle with memorizing and understanding English vocabulary due to monotonous and conventional teaching methods. This study aimed to investigate the effectiveness of using English songs as a teaching medium to improve students’ vocabulary mastery and learning motivation. It employed a quasi-experimental design with a Pretest-Posttest Control Group Design involving all fifth-grade students of MI Ma’arif Surengede Kertek in the academic year 2024/2025, using total sampling technique. The experimental class was taught using several English songs by DJ Raphi, such as Head, Shoulders, Knees, and Toes, Move It, Superstar, and If You're Happy and You Know it, while the control class was taught using conventional methods. Data were collected through vocabulary tests and observation sheets, then analyzed using SPSS Statistics 25 covering validity, reliability, normality, homogeneity, paired sample t-test, and independent sample t-test. The analysis results showed a significant improvement in the experimental group’s post-test scores compared to both their pre-test scores and the control group’s scores, confirming that the use of English songs effectively enhances students’ vocabulary mastery and learning motivation, with statistical tests.